2006
DOI: 10.1037/0021-9010.91.5.987
|View full text |Cite
|
Sign up to set email alerts
|

Workplace aggression in teenage part-time employees.

Abstract: Among adult employees, interpersonal injustice and abusive supervision predict aggression toward supervisors at work. The aim of this study was to assess whether similar relationships exist among teenage employees and, further, whether teenagers' reasons for working moderate these relationships. Multiple regression analyses on data from 119 teenage employees showed that financial and personal fulfillment reasons for working moderate the impact of interpersonal injustice and abusive supervision on aggression di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 90 publications
0
56
0
2
Order By: Relevance
“…Third, the inclusion of both coach and parent leadership allows for a comparison of their respective influence over children's aggression. Fourth, while levels of physical aggression are frequently truncated in research (Dupré, Inness, Connelly, Barling, & Hoption, 2006), the range of aggression found within ice hockey enhances statistical conclusion validity and captures a wider domain of aggression.…”
Section: Study Strengths and Limitationsmentioning
confidence: 97%
“…Third, the inclusion of both coach and parent leadership allows for a comparison of their respective influence over children's aggression. Fourth, while levels of physical aggression are frequently truncated in research (Dupré, Inness, Connelly, Barling, & Hoption, 2006), the range of aggression found within ice hockey enhances statistical conclusion validity and captures a wider domain of aggression.…”
Section: Study Strengths and Limitationsmentioning
confidence: 97%
“…Fourth, despite their prevalence in the workforce, little research attention has been paid to young workers' attitudes, behaviours and work-related experiences (Loughlin and Barling, 2001). For example, the research of Vaez et al (2004) on the frequency of abusive events among young workers and Dupre et al (2006) on workplace aggression as an outcome of abusive supervisor, are among only a handful of studies that have examined young workers' experiences of abusive leadership. As Kets de Vries (2004) argued that past experiences influence present and future experiences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As these both countries are totally different from each other on the basis of their economic situation, religion and especially on their cultural grounds. Aryee, Chen, Sun, & Debrah, 2007;Jian et al, 2011;Wang et al, 2012;Wei & Si, 2013;Xiaqi, Kun, Chongsen, & Sufang, 2012;Xu, Huang, Lam, & Miao, 2012) 2 North America (Tepper, 2000;Tepper 2007;Tepper et al, 2009;Tepper et al, 2006;Tepper, Duffy, Hoobler, & Ensley, 2004;Tepper, Duffy, et al, 2001;Tepper et al, 2008;Tepper, Lockhart, & Hoobler, 2001;Tepper et al, 2011;Tepper et al, 2007;Ashforth, 1994Ashforth, , 1997Bowling & Michel, 2011;Carpenter, Geletkanycz, & Sanders, 2004;Christmas, 2007;DelBel, 2003;Dupré, Inness, Connelly, Barling, & Hoption, 2006;Namie & Namie, 2009;Tsapatsis, 2012) 3 Australia (Grice et al, 2003 ;Ng, 2010 ;Kiazad et al, 2010) 4 United Kingdom (Turnbull, 1995;Deborah, 2000;McMillan, 1995) 5 Pakistan , Khan, 2010Khan, 2014aKhan, , 2014bKhan, , 2014cImran, 2010;Mukhtar et al, 2010;Bashir & Hanif, 2011;Gadit & Mugford, 2008) 6 Israel (Dana Yagil, 2006) 7 Turkey …”
Section: Selection Of Hofstede's Cultural Dimensions For Present Studymentioning
confidence: 99%